Biohydrogen and biomethane production sustained by untreated matrices and alternative application of compost waste. (October 2016) - Arizzi, Mariaconcetta; Morra, Simone; Pugliese, Massimo; Gullino, Maria Lodovica; Gilardi, Gianfranco; Valetti, Francesca
Highlights: Compost was used as the sole substrate for hydrogen and methane production. Hydrogen and methane yields were evaluated for the first time on green compost. Limited amount of added water can sustain biogas production. Low quality compost can have an alternative use in anaerobic digestion plants. Abstract: Biohydrogen and biomethane production offers many advantages for environmental protection over the fossil fuels or the existing physical-chemical methods for hydrogen and methane synthesis. The aim of this study is focused on the exploitation of several samples from the composting process: (1) a mixture of waste vegetable materials (" Mix "); (2) an unmatured compost sample (ACV15); and (3) three types of green compost with different properties and soil improver quality (ACV1, ACV2 and ACV3). These samples were tested for biohydrogen and biomethane production, thus obtaining second generation biofuels and resulting in a novel possibility to manage renewable waste biomasses. The ability of these substrates as original feed during dark fermentation was assayed anaerobically in batch, in glass bottles, in order to determine the optimal operating conditions for hydrogen and/or methane production using " Mix " or ACV1, ACV2 or ACV3 green compost and a limited amount of water. Hydrogen could be produced with a fast kinetic in the range 0.02–2.45 mL H2 g −1 VS, while methane was produced with a slower kinetic in the range 0.5–8 mL CH4 g −1 VS. It was observed that the composition of each sample influenced significantly the gas production. It was also observed that the addition of different water amounts play a crucial role in the development of hydrogen or methane. This parameter can be used to push towards the alternative production of one or another gas. Hydrogen and methane production was detected spontaneously from these matrices, without additional sources of nutrients or any pre-treatment, suggesting that they can be used as an additional inoculum or feed into single or two-stage plants. This might allow the use of compost with low quality as soil improver for alternative and further applications.